The Great Britain’s Influence in the Post-Soviet Space: Socio-Cultural Aspect - Vyacheslav V. Sutyrin (Современная Европа)
The paper is aimed at investigating the recent trends of Britain’s socio-cultural influence in the former USSR republics. The analysis covers London’s major regional programs, financing, mechanisms of influence, and implementing organizations. Subregional differentiation of political approaches is established. Jn Ukraine and Moldova sociocultural influence infrastructures are aimed at direct political influence as well as military and political struggle with Russia. In the South Caucasus London prioritizes broadening influence in the interstate dialogue and conflicts as well as anti-Russian information campaigns with the aim of removing Russian military presence. In Central Asia Britain works on broadening regional footprint through technical and socio-economic programs. The author concludes that preservation of limitrophe status of the former USSR republics constitutes merely one possible mode of British regional policy. The other mode consists of regional order revision which presupposes transition from strengthening a neutral status of post-Soviet states towards instrumentalizing their dependencies on Britain’s influence in the ongoing geopolitical contest with Russia. In the face of transition to a polycentric world order Britain’s development assistance and influence programs evolved in the direction of politicization and weaponization. Hence destabilization risks for post-Soviet states increase. In the context of a ‘unipolar moment’ London was interested in the development of post-Soviet space as a part of global periphery of the Western-centric international system, but not as a part of an alternative geoeconomic pole. Amid the transition to a polycentric world order British system of influence is increasingly coming into conflict with alternative poles hence proliferating destabilization risks for the former USSR republics.